306 IMPACT OF COMBINED GASTRIC AND SACRAL STIMULATORS ON UPPER/LOWER GASTROINTESTINAL AND URINARY SYMPTOMS. Issue 1 (1st January 2007) - Abrasley, C.; Jain, S.; White, P.; Abell, T. L.
Abstract : Introduction: Gastric electrical stimulation (GES) is available as a humanitarian use device for patients with the symptoms of gastroparesis and is effective in reducing gastrointestinal symptoms. We have previously shown that patients with gastric motor disorders often have coexisting abnormalities of the genitourinary system (Gastroenterology 1997;112:A737), which may now be treated with sacral electrical stimulation (SES), resulting in similar improvements in genitourinary symptoms. SES has been shown to be beneficial in controlling fecal incontinence and resistant idiopathic constipation. Patients: We compared the results of therapy with GES and SES in 20 patients who were implanted with both devices. Data for 16 patients are complete for upper and lower gastrointestinal and urinary symptoms. Patients were 18 F, 2 M, mean age of 40 years, who had documented gastroparesis as well as bladder or other pelvic floor dysfunction. All 20 patients had received their GES before the SES. Methods: Patients were evaluated at baseline and latest follow-up (median 4 years for GES and 2 years for SES). Scores of upper GI (GI: 0-4, TSS max 20), lower GI (GI: 0-4, TSS max 12 and BMs per day), and GU (GU: 0-3, UTSS, max 12) function were recorded. Results were compared by paired t -tests and reported as mean ± SE. Results: All 16 patients improved both upper and lower GI and GU symptoms. Improvement in all parameters as nausea (2.75 vs 0.65), vomiting (3.98 vs 1.63), anorexia (3.48 vs 1.45), bloating (3.7 vs 1.98), abdominal pain (3.8 vs 1.4), and gastric total symptom score (TSS) (17.1 vs 7.1), leakage (1.74 vs 0.26), urinary urgency (1.74 vs 0.61), voiding difficulty (2.2 vs 0.38), number of pads used (1.08 vs 0.21) and urinary total symptom score (UTSS) (6.55 vs 1.13), fecal urgency (1.44 vs 1.0), constipation (2.81 vs 1.19), fecal total symptom score (5.0 vs 2.69), and number of BMs per day (1.12 vs 1.87) were statistically significant (Table ). Conclusions: The combination of GES and SES appears to be both safe and effective for patients with concomitant gastroparesis and bladder dysfunction, and SES improved coexistent fecal abnormalities as well.